Analisis Pengaruh Indeks Pembangunan Manusia (Ipm) Terhadap Pertumbuhan Ekonomi Syariah Di Sumatera Utara - Habibah Shobri; Khofifah Sari Hasibuan; M. Daffa Nasution; Juliana Nasution (AGHNIYA : Jurnal Ekonomi Islam, 2022)
This study aims to test whether the Human Development Index (IPM) has a positive effect on regional economic growth in North Sumatra. This study uses a quantitative approach, data obtained through the Central Bureau of Statistics of North Sumatra, the data in this study are time series data from 2017 to 2021. The data analysis method uses linear regression analysis and classical assumption tests with the help of the SPSS program. The results of the study prove that there is a significant positive influence on the Human Development Index (IPM) and Economic Growth variables in North Sumatra.